2012
DOI: 10.1021/ja209981n
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Plasmonic Circular Dichroism of Au Nanorod and DNA Assemblies

Abstract: Reversible plasmonic circular dichroism (CD) responses are realized for the first time based on temperature-dependent assembly and disassembly of Au nanorod (Au NR) and DNA hybrids. Compared with the conventional UV-vis absorption spectra, the changes in both intensity and line shape of plasmonic CD signals are much more pronounced, leading to a preliminary detection limit of DNA as low as 75 nM. The mechanism and influence factors of reversible plasmonic CD responses are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
255
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(261 citation statements)
references
References 36 publications
4
255
0
2
Order By: Relevance
“…For example, it was a powerful method to differentiate a secondary structure of proteins which can appear in the forms of α-helix, random coil, or β-sheet. Recently the concepts of chirality and CD have been brought to the field of plasmonics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . One of the motivations for this development is plasmon-enhanced sensing of chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was a powerful method to differentiate a secondary structure of proteins which can appear in the forms of α-helix, random coil, or β-sheet. Recently the concepts of chirality and CD have been brought to the field of plasmonics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . One of the motivations for this development is plasmon-enhanced sensing of chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic nanoarchitectures have been constructed by bottomup self-assembly and/or top-down lithography, showing a number of applications in diagnostics, energy-harvesting, nanophotonic circuits and so on [28]. Recent studies including our group's results have found that when chiral molecules or their assemblies are in proximity to noble metal nanoparticles, plasmon-induced CD in the visible or near-infrared region will appear owing to transportation of chirality from chiral molecules or templates to nanoparticles [29][30][31]. It should be noted that there have been some reports on the optical activity of gold or silver nanospheres or nanorods that are adsorbed on chiral molecular assemblies, such as DNA [32,33], peptides [34] or artificial chiral molecules [35].…”
Section: Resultsmentioning
confidence: 99%
“…A biocompatible nanoplasmonic device was assembled with the aid of programmable DNA assembly [114], which can control the chirality of plasmonic nanostructures (Fig. 4) [115,116]. A 3D photonic crystal of DNA-labeled plasmonic nanoparticles was fabricated by DNA-programmable crystallization with nanometer precision [117].…”
Section: Plasmonic Devicesmentioning
confidence: 99%